Anomalias de calendário no mercado de capitais brasileiro: Características das firmas, regionalidade e efeitos no desempenho dos fundos de investimento - Borges Junior, Dermeval Martins (2024)
Contextualization – Under the assumptions of the Efficient Market Hypothesis (EMH), there are questions regarding the real ability of sophisticated investors to achieve superior performance compared to other market participants, since, in theory, distinct knowledge about certain information would not bring any benefit in terms of return. However, this does not apply to markets with some inefficiencies. Among the main inefficiencies in this regard, which could be exploited by investors in the pursuit of abnormal returns, there are calendar anomalies, which vary according to the regional characteristics of the markets. Objective – The objective of this research is to investigate the risk-adjusted performance of Brazilian investment funds in order to identify any strategic exploitation of calendar anomalies aimed at achieving extraordinary returns. Method – The sample consisted of daily price data from 669 stocks of listed Brazilian companies, as well as 7,147 Brazilian equity funds with available data from 2005 to 2023. The analysis of stock return seasonality was conducted using generalized autoregressive conditional heteroskedasticity models. The relationship between stocks exposed to anomalies and the funds was based on the composition of their respective portfolios. To estimate the effect of exploiting calendar anomalies on fund performance, we employed linear regression models with panel data. Results – The evidence found suggests that stocks issued by firms with certain characteristics are more susceptible to calendar anomalies. Another finding relates to the identification of temporal cycles in the seasonal return patterns of stocks traded in the Brazilian capital market, consistent with the fundamentals of the adaptive markets hypothesis. Regarding fund performance, the main results indicated that funds with higher monthly allocations to stocks whose returns were subject to seasonality did not show better performance based on the risk-adjusted return metrics considered. This implies that, in the Brazilian market, calendar anomalies do not necessarily represent a resource through which funds achieve extraordinary returns. Adherence of the research to the PPGADM concentration area and research line – The adherence of the research to the PPGADM concentration area and research line is justified considering that calendar anomalies arise from specific inefficiencies in each market, which can be used by managers and investors in resource allocation decisions. In the case of the Brazilian capital market, some of its unique characteristics, such as its level of development, the concentration of company ownership, low savings capacity, and limited financial and investment knowledge among the population can give rise to market inefficiencies with effects particular to this country. Similarly, the regional characteristics of the publicly traded companies issuing the stocks (region of the country and federal unit) were also considered in the context of exploiting calendar anomalies as a potential strategic resource in the composition of investment fund portfolios. Impact and innovative nature – The research innovates by examining the potential exploitation of calendar anomalies as a means for Brazilian investment funds to achieve extraordinary returns. Return seasonality has been extensively studied in the Brazilian stock market; however, little attention has been given to the use of this knowledge in the management of investment funds. Generally, previous studies addressing anomalies in the Brazilian capital market have focused on identifying them and describing their effects. Therefore, it is understood that investigating the use of knowledge about return seasonality as a means of generating value in fund management characterizes the innovation brought by this thesis. Economic, social, and regional impact – From an economic perspective, the results of this research can support decisions by investment funds that lead to improved performance. By identifying market inefficiencies stemming from the calendar and the performance of funds under such conditions, fund managers can employ investment strategies based on seasonal patterns to enhance their performance. The social impact of this research lies in the fact that contributing to the performance efficiency of investment funds, through the generation of knowledge about calendar anomalies, ultimately implies contributing to the efficiency of society's resource allocations as a whole. This is because investment funds, operating as a form of condominium, consist of a pool of resources from various economic agents. Finally, given the understanding that calendar anomalies vary according to regional characteristics of each market, this research includes a regional approach by developing analyses that consider the locations of the companies issuing stocks. Therefore, it can be said that the study advances by providing evidence on the occurrence of seasonal return patterns with regional nuances. Regional implications – The findings support the understanding that the divergence in the determination of calendar anomalies among markets can result from regional aspects. This is because certain regions of the country and federal units exhibited significantly different percentages of stocks with seasonal return patterns in the various calendar anomalies examined. It is understood that these results can contribute to the understanding and development of the Brazilian capital market by considering the regional characteristics of firms in the analysis of calendar anomalies. Sustainable Development Goals addressed in the research – SDG 8 – Decent Work and Economic Growth / Target 8.3 - Promote development-oriented policies that support productive activities, decent job creation, entrepreneurship, creativity, and innovation, and encourage the formalization and growth of micro, small and medium-sized enterprises, including through access to financial services; SDG 10 - Reduced Inequalities / Target 10.6 - Ensure enhanced representation and voice for developing countries in decision-making in global international economic and financial institutions in order to deliver more effective, credible, accountable and legitimate institutions.